2020
DOI: 10.3390/bs10060093
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemography, Geography, and Personality as Determinants of Car Driving and Use of Public Transportation

Abstract: To address the sustainability challenges related to travel behavior, technological innovations will not be enough. Behavioral changes are also called for. The aim of the present study is to examine the influence of sociodemography, geography, and personality on car driving and use of public transportation. Sociodemographic factors have been defined by age, gender, income, and education. Geographic factors have been studied through residential area (e.g., rural and urban areas). Personality has been studied thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
(76 reference statements)
3
10
0
Order By: Relevance
“…A nationally representative study of the Swedish population reports that car driving is influenced by a low degree of Openness, a high degree of Extraversion and a low degree of Neuroticism [23]. The same study reported that use of public transportation is influenced by a high degree of Openness and Agreeableness, and a low degree of Conscientiousness and Extraversion [23].…”
Section: Personality and Choice Of Modes Of Transportmentioning
confidence: 99%
See 4 more Smart Citations
“…A nationally representative study of the Swedish population reports that car driving is influenced by a low degree of Openness, a high degree of Extraversion and a low degree of Neuroticism [23]. The same study reported that use of public transportation is influenced by a high degree of Openness and Agreeableness, and a low degree of Conscientiousness and Extraversion [23].…”
Section: Personality and Choice Of Modes Of Transportmentioning
confidence: 99%
“…A nationally representative study of the Swedish population reports that car driving is influenced by a low degree of Openness, a high degree of Extraversion and a low degree of Neuroticism [23]. The same study reported that use of public transportation is influenced by a high degree of Openness and Agreeableness, and a low degree of Conscientiousness and Extraversion [23]. In contrast, a study on the Big Five personality traits and use of public transportation in Tehran (Iran) reports that use of public transportation is positively related to Extraversion and negatively related to Neuroticism [1].…”
Section: Personality and Choice Of Modes Of Transportmentioning
confidence: 99%
See 3 more Smart Citations